Field-controlled tunability of novel multifunctional phenomena in Tb-substituted La2CoMnO6: Role of antisite disorder. Issue 24 (15th December 2021) - Pal, Arnab; Feng, Zhenjie; Wu, Hao; Li, Tao; Wang, Ke; Si, Jingying; Chen, Jiafeng; Chen, Yanhong; Chen, Fei; Ge, Jun-Yi; Cao, Shixun; Zhang, Jincang
Abstract: Multifunctional materials have gained huge attention owing to their great possibility in device applications. However, producing single-phase multifunctional materials, associated with various novel properties, has been proved to be a serious challenge. A simple yet effective way to overcome this barrier, is therefore of great importance. Here, we report the evolution of temperature- and magnetic field-dependent novel multifunctional phenomena in polycrystalline La2- x Tb x CoMnO6 . Substitution of Tb in ferromagnetic La2 CoMnO6, induces antiferromagnetic ordering through development of antisite disorder and antiphase boundaries, and results in a phase separation between ferromagnetic/antiferromagnetic layers. This originates the coexistence of conventional and inverse magnetocaloric effects in this system. The switching between them, with its tunability with temperature and magnetic field, suggests a huge potential of this compound. In addition, a clear correlation is established between the magnetocaloric switching and field-induced metamagnetic transitions. Furthermore, the discovery of tunable giant exchange bias ( 1.8 kOe) at very low cooling field (500 Oe), a reasonable self-exchange bias (270 Oe), and a large negative magnetoresistance ( 14%), makes this system enormously attractive for practical applications and fundamental research. The present study proposes a novel and effective route for successfully preparing essential multifunctional compounds to open a new pathway toward room-temperature applications.